Passive financing in the crosshairs: CFIUS intensifies focus on limited partners in covered private equity transactions - Daniel J. Gerkin; Michelle A. Weinbaum (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
CFIUS is increasingly shifting focus from general partners that control investment funds to limited partners that pose minimal-if any-national security risk, leading to unintended consequences. This Perspective argues that CFIUS should prioritize higher-risk investment activity and mitigate the chilling effect on much-needed passive investment in U.S. businesses.
Keywords: 330